Ischaemic and bleeding risk in atrial fibrillation with and without peripheral artery disease and efficacy and safety of full- and half-dose edoxaban vs. warfarin: insights from ENGAGE AF-TIMI 48. Issue 7 (28th December 2021) - Bonaca, Marc P; Antman, Elliott M; Cunningham, Jonathan W; Wiviott, Stephen D; Murphy, Sabina A; Halperin, Jonathan L; Weitz, Jeffrey I; Grosso, Michael A; Lanz, Hans J; Braunwald, Eugene; Giugliano, Robert P; Ruff, Christian T
Abstract: Aims: In patients with atrial fibrillation (AF), peripheral artery disease (PAD) is associated with higher rates of stroke and bleeding. Both higher dose edoxaban (60/30 mg) and lower dose edoxaban (30/15 mg) were non-inferior to warfarin for stroke and systemic embolism (SSE) and significantly reduced major bleeding in AF patients in the global study to assess the safety and effectiveness of edoxaban vs standard practice of dosing with warfarin in patients with atrial fibrillation (ENGAGE AF-TIMI 48) trial. Whether the efficacy and safety of these dosing strategies vs. warfarin are consistent in patients with AF and PAD has not been described. Methods and results: Of 21 105 patients with AF randomized to warfarin, edoxaban 60/30 mg, or edoxaban 30/15 mg, 841 were identified with PAD. Endpoints included major adverse cardiovascular events (MACEs), SSE, and major bleeding. Patients with PAD had higher risk of MACEs [adjusted hazard ratio (HRadj ) 1.33, 95% confidence interval (CI) 1.12–1.57, P = 0.001] and cardiovascular (CV) death (HRadj 1.49, 95% CI 1.21–1.83, P < 0.001) than those without PAD, but not major bleeding. The efficacy of edoxaban 60/30 mg vs. warfarin was consistent regardless of PAD (SSE HR; PAD 1.16, 95% CI 0.42–3.20; no-PAD 0.86, 95% CI 0.74–1.02, P -interaction 0.57) as was major bleeding (PAD 0.96, 95% CI 0.54–1.70; no-PAD 0.80, 95% CI 0.70–0.91, P -interaction 0.54). Edoxaban 30/15 mg was inferior for SSE, with significant heterogeneity when stratified by PAD status ( P -interaction 0.039). Conclusion: Patients with AF and PAD are at heightened risk of MACEs and CV death vs. those without PAD. The efficacy and safety of edoxaban 60/30 mg vs. warfarin in AF are consistent regardless of PAD; however, edoxaban 30/15 mg is inferior for stroke prevention in AF patients with PAD. Clinical Trial Registration : ClinicalTrials.gov identifier: NCT00781391 Graphical Abstract: